Draft genome and description of Microvirga mediterraneensis strain Marseille-Q2068T sp. nov., a new bacterium isolated from human healthy skin. (March 2021) - Boxberger, M.; Ben Khedher, M.; Magnien, S.; Cassir, N.; La Scola, B.
Abstract: In 2019, by culturing a skin swab from the forehead of a 70-year-old healthy woman via the culturomics method, we isolated the new bacterial strain Marseille-Q2068T (= CSUR-Q2068). Matrix-assisted desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) failed to identify this isolate. Analysis of the 16S ribosomal RNA gene and genome-to-genome comparison suggested that this taxon belongs to a novel bacterial species within the family Methylobacteriaceae in the phylum Proteobacteria. We describe here its main phenotypic characteristics, genome sequence and annotation of Microvirga mediterraneensis strain Marseille-Q2068T, a new member of the Microvirga genus, which we propose as the type strain.